Kontekstualisasi Hadis Hak Ijbar dalam Perjodohan di Indonesia - Rahmawati, Theadora; Zakiyuddin Abdul Adhim (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2023)
This article focuses on the study of the right of ijbar for marriage guardians in arranged marriages referring to the right of women to choose their own life partners with cultural, social and religious perspectives. This research is a library research with literature sources using books, and related journals. It is descriptive-analytical in nature by describing ijbar rights in marriage and contextualized traditions. The formulation of the problem is first, the contextualization of the traditions regarding the mujbir guardian in Indonesia. Second, the factors behind arranged marriage in Indonesia. As a result, the contextualization of the authority of the right of ijbar given to the guardian to his daughter is a form of assistance and responsibility of parents to the child so that the child's household life becomes harmonious. In addition, it does not plunge children into parental choices that lead to mischief. Factors behind the occurrence of arranged marriage. First, Internal factors such as difficulties in finding a matchmaking partner Second, external factors, namely: social culture, religious understanding.)